Detection of sex hormone level in hemodialysis female patients with end-stage renal disease of childbearing age and its relationship with serum 25 hydroxyvitamin D - Zhang Jiu-zhi; Guo Jie; Li Jiang (Linchuang shenzangbing zazhi)
Objective To explore the relationship between sex hormone levels and serum 25 hydroxyvitamin D[25（OH）D]in female patients of childbearing age with end-stage renal disease on hemodialysis（HD）.Methods From May 2016 to November 2019,91 female HD patients of childbearing age with end-stage renal disease（dialysis group）and 87 healthy controls（healthy group）were selected during the same period.And the levels of sex hormones including luteinizing hormone（LH）,follicle stimulating hormone（FSH）,prolactin（PRL）,estradiol（E2）,progesterone（P）,testosterone（T）and serum 25（OH）D were detected.Sex hormone parameters and serum level of 25（OH）D were compared between two groups and the relationship between the levels of LH,FSH,PRL,E2,P,T and 25（OH）D in dialysis group was analyzed by Pearson’s correlation.Results The serum levels of LH,FSH and PRL were higher in dialysis group than those in healthy group.And the levels of E2,P and T were lower in dialysis group than those in healthy group and the differences were significant（P<0.05）.The serum level of 25（OH）D was significantly lower in dialysis group than that in healthy group（P<0.05）.The total ratio of vitamin D deficiency or insufficiency was 83.52% in dialysis group and it was significantly higher than that of healthy group（12.64%）（P<0.05）.Significant negative correlations existed between serum LH/FSH and 25（OH）D（P<0.05）and a significant positive correlation existed between serum E2 and 25（OH）D（P<0.05）.However, no significant correlation existed between serum levels of PRL,P,T and 25（OH）D（P>0.05）.Conclusion Female HD patients of childbearing age with end-stage renal disease have sex hormone disorder and vitamin D deficiency or insufficiency.And the levels of LH,FSH and E2 are correlated with serum level of 25（OH）D.